KovaaK's aim trainer as a reliable metrics platform for assessing shooting proficiency in esports players: a pilot study - Rogers, Ethan J.; Trotter, Michael G.; Johnson, Daniel; Desbrow, Ben; King, Neil (Frontiers in Sports and Active Living, 2024)
Esports research lacks game-based metrics platforms appropriate for adequately capturing esports performance. The aim of this pilot study was to assess the reliability of the KovaaK's first-person shooter (FPS) aim trainer as a metrics platform for assessing shooting proficiency in esports players. Ten FPS esports players completed two identical experimental trials (T) separated by three to five days. Each trial included four rounds (R) of testing, evaluating four shooting tasks: Micro Flicking, Macro Flicking, Strafe Tracking, and Wall Peeking. Reliability of performance outcomes (e.g., accuracy, headshot accuracy, hits per second, and total shots hit) were assessed using the intraclass correlation coefficient (ICC) and their 95% confidence intervals (CI), and significant differences were identified using repeatedmeasures analysis of variance (RM-ANOVA). Results indicated excellent, or good to excellent reliability for all outcome variables with the ICC estimates ranging between 0.947-0.995, with lower and upper bound 95% CIs ranging between 0.876-0.988, and 0.984-0.999, respectively. Significant improvements were seen between experimental trials in the Macro Flicking task for accuracy (p = .005) and hits per second (p = .009) only. Significant interactions between trial and round were identified in the Micro Flicking task for accuracy (p = .006), with post hoc analysis showing accuracy was significantly higher in T1R1 compared to T2R1 (87.74 ± 3.13 vs 85.99 ± 3.05, respectively, p = .02), and in T2R4 compared to T2R2 (87.99 ± 2.89 vs 84.70 ± 4.25, respectively, p = .049). Significant interactions were also identified in the Strafe Tracking task for headshot accuracy (p = .002), with post hoc analysis showing headshot accuracy was significantly higher in T1R2 compared to T2R2 (78.48 ± 8.15 vs 76.79 ± 12.16, respectively, p = .003), and in T1R2 compared to T1R1 (78.48 ± 8.15 vs 73.68 ± 17.94, respectively, p = .023). In ASSESSING SHOOTING PROFICIENCY IN ESPORTS 2 summary, this study demonstrates that KovaaK's provides a reliable metrics platform for assessing shooting proficiency in esports, however, some variability in performance was observed.